Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1042/bsr20204124
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes and the role of PDK4 in CD14+ monocytes of coronary artery disease

Abstract: Background. Coronary artery disease (CAD) is a chronic inflammatory disease caused by development of atherosclerosis, which is the leading cause of mortality and disability. Our study aimed to identify the differentially expressed genes (DEGs) in CD14+ monocytes from CAD patients compared with those from non-CAD controls, which might pave the way to diagnosis and treatment for CAD. Methods. The RNA-seq was performed by BGISEQ-500, followed by analyzing with R package to screening differentially expressed genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…One group reported that PDK inhibition with dichloroacetate led to decreased protein levels of the pro-inflammatory cytokines IL-1β and TNF-α, as well as the anti-inflammatory cytokine IL-10 (Xuewei Zhu et al, 2020). Another group reported that mRNA levels of PDK4 were higher in CD14 + monocytes from coronary artery disease patients relative to healthy controls, and were further increased by exposure to low density lipoprotein (Du et al, 2021). Thus, there are multiple examples from literature where enhanced oxidative phosphorylation is speculated to be both anti-inflammatory and pro-inflammatory, depending on the context and, likely, the magnitude of change.…”
Section: Discussionmentioning
confidence: 99%
“…One group reported that PDK inhibition with dichloroacetate led to decreased protein levels of the pro-inflammatory cytokines IL-1β and TNF-α, as well as the anti-inflammatory cytokine IL-10 (Xuewei Zhu et al, 2020). Another group reported that mRNA levels of PDK4 were higher in CD14 + monocytes from coronary artery disease patients relative to healthy controls, and were further increased by exposure to low density lipoprotein (Du et al, 2021). Thus, there are multiple examples from literature where enhanced oxidative phosphorylation is speculated to be both anti-inflammatory and pro-inflammatory, depending on the context and, likely, the magnitude of change.…”
Section: Discussionmentioning
confidence: 99%
“…PDK4 dysfunction was further plausibly linked with insulin resistance and/or diabetes-associated end-stage renal disease and renal transplantation [ 32 ]. As PDK4 also plays an important role in vascular-related diseases, it might also be associated with nephroangiosclerosis [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that altered expression of DDX58 [413], STAT1 [414], TLR4 [415], CYP2D6 [416], JAK2 [417], TLR2 [418], DUSP6 [419], HDAC9 [420], LATS2 [421], CA2 [150], HIPK3 [422], CCR2 [423], GAB1 [120], UFL1 [424], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [425], PRKAR1A [265], SIRT1 [426], FGL2 [427], TET2 [428], ASCC2 [429], BIN1 [430], HSPB1 [431], IGFBP4 [432], TRPM4 [433] and LGALS3 [434] might be associated with the progression of heart failure. STAT1 [435], TLR4 [436], ABCA1 [437], PTGS2 [68], CYP2D6 [438], CR1 [439], PDK4 [440], RNF213 [441], ZDHHC17 [70], TLR8 [442], PDGFC (platelet derived growth factor C) [443], TLR2 [444], CYP1B1 [445], HDAC9 [446], IL1RN [447], GCH1 [448], EGR1 [449], ZEB2 [450], PLA2G7 [451], CCR2 [452], GCLC (glutamate-cysteine ligase catalytic subunit) [258], VEGFA (vascular endothelial growth factor A) [453], CD46 [454], NFKBIZ (NFKB inhibitor zeta) [455], LDLR (low density lipoprotein receptor) [456], TLR6 [457], SIRT1 [458], NOD2 [459], FGL2 [460], IDH1 [461], TET2 [462], PFKFB2 [463], KDM6A [464], IKZF2 [465], ZNF606 [466], PF4 [467], CCR7 [468], RUNX3 [469], TCF7 [470], PPBP (pro-platelet basic protein) [471], IGFBP4 [280], HSPG2 [472] and LGALS3 [236] expression might be regarded as an indicator of susceptibility to CAD. STAT1 [473], TLR4 [367], JAK2 [474], PDGFC (platelet derived growth factor C) […”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that altered expression of DDX58 [413], STAT1 [414], TLR4 [415], CYP2D6 [416], JAK2 [417], TLR2 [418], DUSP6 [419], HDAC9 [420], LATS2 [421], CA2 [150], HIPK3 [422], CCR2 [423], GAB1 [120], UFL1 [424], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [425], PRKAR1A [265], SIRT1 [426], FGL2 [427], TET2 [428], ASCC2 [429], BIN1 [430], HSPB1 [431], IGFBP4 [432], TRPM4 [433] and LGALS3 [434] might be associated with the progression of heart failure. STAT1 [435], TLR4 [436], ABCA1 [437], PTGS2 [68], CYP2D6 [438], CR1 [439], PDK4 [440], RNF213 [441], ZDHHC17 [70], TLR8 [442], PDGFC (platelet derived growth factor C) [443], TLR2 [444], CYP1B1 [445], HDAC9 [446], IL1RN [447], GCH1 [448], EGR1 [449], ZEB2 [450], PLA2G7 [451], CCR2 [452], GCLC (glutamate-cysteine ligase catalytic subunit) [258], VEGFA (vascular endothelial growth factor A) [453], CD46 [454], NFKBIZ (NFKB inhibitor zeta)…”
Section: Construction Of the Tf-hub Gene Regulatory Networkmentioning
confidence: 99%